Conjunto de ejercicios para la mujer en etapa reproductiva, de la comunidad de Jibacoa, municipio Manicaragua - Mederos Chirino, Yeney (Universidad de Ciencias de la Cultura Física y el Deporte "Manuel Fajardo"., 2013)
One of the big challenges of the medicine and of all those institutions that offer the promotion of health constitutes physical and psychological preparation of the pregnant. One of the factors that has influenced in a notorious way in the increasing of the expectation of life and their quality in the population, is the well directed systematic physical activity. However, in the community Jibacoa of the municipality Manicaragua, There is a tendency to risk pregnancies, for what pregnant don't carry out the exercises of the program “Gymnastics for pregnant”, hence from the problemic situation, the following scientific problem arises: How to contribute to the prevention of the risk factors of the pregnancy in women in reproductive stage of the community of Jibacoa? To answer the scientific problem, it is defined as General objective, to design a plan of preparation activities for the prevention of risk factors in women in the reproductive stage in the community of Jibacoa municipality in Manicaragua. In the diagnosis of the situation of the community, different methods and investigation instruments of the theoretical level were used such as the statistical empirical and mathematical level. tarting from the results of the diagnosis, and taking into account the possibilities of the Physical Culture, a group of exercises was designed directed to women in the reproductive stage, for what e different exercises of the program of the Physical Culture were selected, combined with those of the program of “Gymnastics for pregnant”. This proposal was assessed positively by the performers, as well as for the technician of the Physical Culture.

Uno de los grandes retos de la medicina y de las instituciones de salud lo constituye la preparación física y psicológica de la embarazada. Uno de los factores que ha influido en el aumento de la expectativa de vida y su calidad en la población es la actividad física sistemática bien dirigida. Sin embargo en la comunidad Jibacoa del municipio Manicaragua, existe una tendencia a embarazos de riesgo, por lo que las gestantes no realizan los ejercicios del programa “Gimnasia para embarazadas”, de ahí que a partir de la situación problémica, nos surge el siguiente problema científico: ¿Cómo contribuir a la prevención de los factores de riesgo del embarazo en la mujer en etapa reproductiva de la comunidad de Jibacoa? .Para dar respuesta al problema formulado, se define como objetivo general diseñar un conjunto de ejercicios de preparación, para la prevención de factores de riesgo en la mujer en etapa reproductiva en el poblado de Jibacoa. En el diagnóstico de la situación de la comunidad, se utilizaron diferentes métodos e instrumentos de investigación tanto del nivel teórico como del nivel empírico y matemático estadístico. A partir de los resultados del diagnóstico y teniendo en cuenta las posibilidades de la Cultura Física, se diseñó un conjunto de ejercicios dirigidos a la mujer en etapa reproductiva, para lo cual se seleccionaron ejercicios de diferentes programas de la Cultura Física combinados con los del programa de Gimnasia para embarazadas. Esta propuesta fue valorada positivamente por las ejecutantes, así como por el técnico de la Cultura Física.
Keywords: Salud; Jibacoa; Manicaragua; Ejercicio Físico; Mujeres Embarazadas; Pregnant Women